KOORDINASI PEMERINTAHAN DALAM MEWUJUDKAN TERTIB ADMINISTRASI PENDUDUK RENTAN DI KOTA PALU PROVINSI SULAWESI TENGAH - B, Asri; Fatahilah, Adee (Program Studi Studi Kependudukan dan Pencatatan Sipil, 2019)
ABSTRACT It is important to making systematic, coordinated and integrated for create collection data of population and handling between agencies in Palu city, to obtain valid data about the number of street children, vagrants, beggars, livelihoods and decent living because the number of them is always increased, so it must be handled in effective and efficient way. The purpose of research is to understand the basic tasks and functions of the of Population and Civil Registration Office, and knowing the orderly administration of vulnerable residents, and also to know the outcome process of realizing the orderly administration of vulnerable populations. The conclusion of this study is coordination of Organization of Regional Devices in the data collection of vulnerable population in Palu City is adjusting the main tasks and functions of each agency, and the each instances still have sectoral ego so it make obstacles in coordination conducted on vulnerable population, and facilities and infrastructure owned by the government of Palu City in dealing with vulnerable residents are still inadequate. The organization of the regional apparatus in the data collection on street children, homeless and beggars has made an effort to resolve the problem by conducting coordination meetings to do the main job list division in accordance of each agency function. Keywords: orderly administration, streed children, homeless people, beggars ABSTRAK Pentingnya melakukan pandataan sistematik, terkoordinasi dan terintegrasi dalam pendataan kependudukan dan penanganan antara instansi di Kota Palu agar mendapatkan data jumlah anak jalanan, gelandangan dan pengemis yang valid serta bantuan penghidupan dan kehidupan yang layak karena jumlahnya yang semakin banyak sehingga harus di tangani dengan cara yang efektif dan efisien. Tujuan penelitian ini adalah untuk memahami tugas pokok dan fungsi Dinas Kependudukan dan Pencatatan Sipil, mengetahui tertib administrasi penduduk rentan, serta untuk mengetahui Hasil Kerja dari proses mewujudkan tertib administrasi Penduduk rentan. Kesimpulan yang di dapatkan adalah koordinasi Organisasi Perangkat Daerah dalam pendataan penduduk rentan di Kota Palu dilakukan dengan menyesuaikan terhadap tugas pokok dan fungsi masing-masing tiap instansi, dan masih adanya ego sektoral antar instansi sehingga menimbulkan hambatan dalam koordinasi yang dilakukan terhadap penduduk rentan dan masih kurangnya sarana dan prasarana yang dimiliki oleh pemerintah Kota Palu dalam menangani para penduduk rentan. Organisasi Perangkat Daerah dalam pendataan kependudukan terhadap anak jalanan, gelandangan dan pengemis telah melakukan upaya mengatasi masalah yang menjadi hambatan dengan melakukan rapat koordinasi kembali untuk dilakukan pembagian tugas yang sesuai dengan fungsi masing-masing instansi tersebut. Kata kunci: tertib administrasi, anak jalanan, gelandangan dan pengemis